"In-Vitro Comparative Study of the Influence of Post Space Preparation Timing On Apical Sealing of Root Canal " (Journal of Hama University, 2020)
The aim of this study is to compare the influence of timing of post space preparation(after 24hours, after one week) and method of post space preparation (mechanical with/without solvents)  on apical root canal sealing. The sample included 40 single root and canal teeth which were uniformed in length to 16 mm from the apex and divided into 4 experimental groups (n=10 teeth each) according to method of post space preparation, as follows: (group #1: lateral condensation/rotary preparation without solvent, group #2: lateral condensation/rotary preparation with solvent. In addition, 2 control groups (group #1: lateral condensation/ manual preparation without solvent, group #1: lateral condensation/ manual preparation with solvent), Where was used resin sealer ADSEAL. and divided the four groups to two halves: the first half was prepared post space after 24hours, the other half was prepared post space after one week. The external root surface was painted with two layers of nail polish except the most apical 2mm. The apical part was immersed with methylene blue for 24 hours. The apical sealing was measured under an endodontic microscope after making longitudinal sections. The data obtained was statistically analyzed using Kruskal-Wallis. The results show that there was no significant difference for timing and method of post space preparation. (P